Mass Media Analysis and Exposure of Bangga Kencana Program towards Youth in North Sumatera Province, Indonesia - Muhammad Ancha Sitorus; Milna Chairunnisa; Sandy Armando Saputra; Debyana Debyana (Randwick International of Social Science Journal, 2022)
The use of mass media as a form of public perception of a program must be a concern so that the success of a program can be measured properly. North Sumatra Province is a province that is divided into three regional segmentations, namely the coast, the central mountains, and the archipelago which are divided into 33 districts/ cities. Analysis of 2019 SKAP BKKBN data. The number of adolescents from the 2019 SKAP data was 1834 people who were the total sample of adolescents in this pellet. This research is descriptive analytic in the form of a secondary data study or analysis, which is to further analyze existing data sets or those that have been collected from the 2019 North Sumatra Province Accountability Program Performance Survey (SKAP). The analysis uses chi-square for bivariate and multiple multiple regressions for multivariate analysis. The results of the study consisted of descriptive and analytic. The description of this research The condition of the IEC media used in informing teenagers in North Sumatra on the pride issues of kencana still rely on print media, electronic media, outdoor media and online media. Its effectiveness is also influenced by the level of education, gender, area of ​​residence, and also the age of adolescence. Electronic media is still popular as a medium that informs youthful issues of good fortune, followed by online media which is a percentage more acceptable to teenagers.